2005
DOI: 10.1111/j.1742-4658.2005.05063.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant hemoglobin βG83C‐F41Y

Abstract: We have engineered a stable octameric hemoglobin (Hb) of molecular mass 129 kDa, a dimer of recombinant hemoglobin (rHb betaG83C-F41Y) tetramers joined by disulfide bonds at the beta83 position. One of the major problems with oxygen carriers based on acellular hemoglobin solutions is vasoactivity, a limitation which may be overcome by increasing the molecular size of the carrier. The oxygen equilibrium curves showed that the octameric rHb betaG83C-F41Y exhibited an increased oxygen affinity and a decreased coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…From uv-visible absorption, and synchronous fluorescence spectroscopic measurements, it was revealed that HbE starts disintegrating or melting at a lower temperature (~ 38°C) compared to that of HbA (~ 42°C) and HbA 2 (~ 45°C) at physiological pH range. These melting temperatures are comparable with the same at high alkaline pH, though a recent study indicated that the melting of HbA starts at much higher temperature (72°C) compared to the value reported here [ 40 ]. Though direct in vitro measurement of thermal stability of HbE was not performed before, earlier studies on other unstable Hb variants along with HbA and HbA 2 have shown that thermal stability of HbA 2 to be the highest among others studied [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…From uv-visible absorption, and synchronous fluorescence spectroscopic measurements, it was revealed that HbE starts disintegrating or melting at a lower temperature (~ 38°C) compared to that of HbA (~ 42°C) and HbA 2 (~ 45°C) at physiological pH range. These melting temperatures are comparable with the same at high alkaline pH, though a recent study indicated that the melting of HbA starts at much higher temperature (72°C) compared to the value reported here [ 40 ]. Though direct in vitro measurement of thermal stability of HbE was not performed before, earlier studies on other unstable Hb variants along with HbA and HbA 2 have shown that thermal stability of HbA 2 to be the highest among others studied [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, after a 15 min incubation of HbA with Hp at room temperature, the SEC profile shows the presence of a single peak (Ve = 9.85 ml) corresponding to the elution volume of the Hp( αβ ) 2 complex (results not shown) [17]. When the same experiment was performed with the β octamer, the SEC profile of this mixture shows the presence of two species corresponding to free Hp1-1(Ve = 10.3 ml) and free β octamer (Ve = 11.6 ml), indicating that the β octamers do not react with Hp after 15 min of incubation (Figure 3(a), red profile) [17]. For the α octamer (Figure 3(b), pink profile) there was about 6% of a Hp/ α octamer complex (Ve = 8.5 ml), in addition to the main species corresponding to free Hp (Ve = 10.3 ml) and free α octamer (Ve = 11.6 ml).…”
Section: Resultsmentioning
confidence: 99%
“…As previously described, the experiments were run at 29°C as a function of pH in 0.1 M sodium phosphate buffer and contained 0.1 mM Hb (on a heme basis) [13, 14,17]. The P 50 values (in mmHg) and the n 50 values are given with an accuracy of ± 10%.…”
Section: Methodsmentioning
confidence: 99%
“…This is reminiscent of the genetically engineered species consisting of two fused tetramers that is presented as a functional octamer. 73,75,76 Dendrimeric assemblies Reaction of hemoglobin with trimesoyl tris(3,5-dibromosalicylate) (TTDS, Fig. 9) forms a bb cross-linked protein with the residual ester available to function as an acylation site for conjugation reactions with nucleophiles.…”
Section: Tetramer-tetramer Interactionsmentioning
confidence: 99%